2021
DOI: 10.1109/ojemb.2021.3053215
|View full text |Cite
|
Sign up to set email alerts
|

Face Coverings, Aerosol Dispersion and Mitigation of Virus Transmission Risk

Abstract: The SARS-CoV-2 virus is primarily transmitted through virus-laden fluid particles ejected from the mouth of infected people. Face covers can mitigate the risk of virus transmission but their outward effectiveness is not fully ascertained. Objective: by using a background oriented schlieren technique, we aim to investigate the air flow ejected by a person while quietly and heavily breathing, while coughing, and with different face covers. Results: we found that all face covers without an outlet valve reduce the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 98 publications
4
80
0
2
Order By: Relevance
“…Mechanistic evidence has demonstrated source control efficacy of medical masks in reducing influenza virus and human seasonal/endemic coronaviruses respiratory emissions from symptomatic individuals [291,496,497], as well as some protection against influenza virus afforded to the wearer [498]. Likewise, fluid dynamics simulation and experimental studies support the role of masks in limiting the spread of respiratory emissions [348,[499][500][501][502].…”
Section: Toward a Multidisciplinary Agreement On Actionable Terminologymentioning
confidence: 95%
See 1 more Smart Citation
“…Mechanistic evidence has demonstrated source control efficacy of medical masks in reducing influenza virus and human seasonal/endemic coronaviruses respiratory emissions from symptomatic individuals [291,496,497], as well as some protection against influenza virus afforded to the wearer [498]. Likewise, fluid dynamics simulation and experimental studies support the role of masks in limiting the spread of respiratory emissions [348,[499][500][501][502].…”
Section: Toward a Multidisciplinary Agreement On Actionable Terminologymentioning
confidence: 95%
“…In the face of limited data, face shields or visors have been suggested to provide some advantages over face masks in terms of eye protection, frontward airflow protection, no hand-toface contact, breathability, full-face visibility, reuse, and disinfection [261,[517][518][519][520]. However, variable design (shape, materials) of face shields and upward, downward, and sideways leakage jets from the edges, seams, and joints are major issues [482,500,[521][522][523]. Face shields are therefore considered to provide a level of eye protection only [55,424].…”
Section: Toward a Multidisciplinary Agreement On Actionable Terminologymentioning
confidence: 99%
“…Airborne transmission happens when a susceptible person inhales microscopic bio-aerosols in the air which are generated from a respiratory event such as a cough, sneeze, or even just breathing and talking [2,5]. While larger droplets (�100μm) reach the ground within a second, aerosols can linger in the air for hours, increasing the probability of a susceptible person coming in contact with the virus [6,7]. For this reason, mask fit is important.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies with human subjects and manikins show that mask usage can limit the droplet and airborne transmission of various infections to and from the wearer [8][9][10][11][12][13][14][15][16]. Air leakage has been observed around the perimeter of the mask where it does not make a seal with the face, reducing the effectiveness of the mask [6,17]. Perimeter leakage is caused by loose or improper fitting face masks and can be significantly impacted by facial features [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Viola et al did this and demonstrated significant leakage jets that may present major hazards. 31 But their study examined coughing where droplets were 50 μm in diameter and peak velocity was 8 m/s despite wearing masks.…”
Section: Discussionmentioning
confidence: 99%